192k views
5 votes
Can someone help me solve this and explain it to me?
−1/6(x−18)+1/3(x+3)=x+4

1 Answer

10 votes

Answer:

Below.

Explanation:

So calculate.

-1/6x+3+1/3x+1=x+4.

Cancel equal terms.

-1/6x+4+1/3x=x+4

Multiply both sides -1/6x+1/3x=x

collect like terms.

-x+2x=6x

move the variable from right to left.

x=6x

collect like terms

x-6x=0

Divide both sides

-5x=0

x=0

User Andie Hunt
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.